2016
DOI: 10.1097/md.0000000000004874
|View full text |Cite
|
Sign up to set email alerts
|

Tumor growth rate of invasive breast cancers during wait times for surgery assessed by ultrasonography

Abstract: Several studies suggest that delay in the surgical treatment of breast cancer is significantly associated with lower survival. This study evaluated the tumor growth rate (TGR) of invasive breast cancers during wait times for surgery quantitatively using ultrasonography (US) and identified clinicopathologic factors associated with TGR.This retrospective study was approved by our institutional review board and the requirement for written informed consent was waived. Between August 2013 and September 2014, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 29 publications
(36 reference statements)
6
57
1
Order By: Relevance
“…While delays in breast cancer treatment are associated with tumor growth, especially in triple negative molecular subtypes which can reach specific growth rates of up to 1.003% per day [20], the relationship between treatment delays and survival is more controversial. Given its significant effect on tumor growth, the presence of a triple negative molecular subtype may conceivably lead to doubts about the necessity of pre-operative MRI delays [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While delays in breast cancer treatment are associated with tumor growth, especially in triple negative molecular subtypes which can reach specific growth rates of up to 1.003% per day [20], the relationship between treatment delays and survival is more controversial. Given its significant effect on tumor growth, the presence of a triple negative molecular subtype may conceivably lead to doubts about the necessity of pre-operative MRI delays [20].…”
Section: Discussionmentioning
confidence: 99%
“…Given its significant effect on tumor growth, the presence of a triple negative molecular subtype may conceivably lead to doubts about the necessity of pre-operative MRI delays [20]. However, Love et al have shown that despite a larger tumor size and more frequent axillary node involvement, delays of less than 6 months had no statistically significant impact on survival [21].…”
Section: Discussionmentioning
confidence: 99%
“…The TVDT is one of the most critical parameters used to develop the consolidated mathematical growth model of the PT and sdMTSs of BC (CoMPaS) and to calculate the earliest diagnostic period of sdMTSs in patients with BC [ 21 ]. The TVDT, which helped in the development of the mathematical growth model, is a combined quality indicator that reflects the subtype of BC, the proliferative activity, the degree of tumor differentiation, the Nottingham prognostic index (NPI) score, receptor activity (ER(+), ER(−), PR(+), PR(−), HER2(+), HER2(−), Ki-67), and triple-negative BC [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Hence, patients can obtain a personalized approach for building a schedule of multimodal examinations to detect sdMTSs at the early stage and to start early treatment that can increase the patient’s life [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growth rate of the PT in patients with BC is calculated via TVDT PT [ 36 , 37 , 38 , 39 , 44 , 45 , 46 , 47 ]. An ultrasound-based diagnosis allows a better detection of the changes in PT sizes in patients with BC to calculate TVDT PT [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Potential clinical applications for the computational modeling of breast cancer include: Monitoring tumor response to cancer treatment over other imaging modalities; tracking tumor growth over time, including from presentation to surgical removal 53 ; and hyperthermia cancer treatment [49][50][51][52] .…”
Section: The High (mentioning
confidence: 99%